Una versión nacionalcatólica de la historia antigua del Próximo Oriente: Las primeras civilizaciones de Luis Suárez Fernández - Vidal Palomino, Jordi (Historiografías, 2021)
The purpose of this paper is to rethink the manual Las primeras civilizaciones by Luis Suárez Fernández, 40 years after its publication. This work examines the academic context in which Las primeras civilizaciones emerged (absence of Near Eastern Studies in Spain), as well as its National Catholic bias with which was written.